Proximate and physical analyses of crackers incorporated with red seaweed, Kappaphycus alvarezii - Adella Anding Aganduk; Patricia Matanjun; Tan, Tek Song; Khor, Ban Hock (Springer, 2024)
The red alga Kappaphycus alvarezii is a versatile food ingredient widely used in the food industry due to its many functional properties. The aim of this study is to substitute wheat four with K. alvarezii powder and determine the efects it has on the physical properties and proximate composition of snack crackers. The six formulations of crackers incorporating diferent proportions of K. alvarezii powder were (C) 0%, (F1) 1%, (F2) 2.5%, (F3) 5%, (F4) 7.5%, and (F5) 10%. Physical analyses such as colour, water activity, and texture as well as proximate analysis of moisture, ash, crude fat, crude protein, and crude fbre content was conducted. The result showed a signifcant (p<0.05) decrease in colour and water activity with the addition of K. alvarezii powder. Meanwhile, proximate analysis showed a signifcant (p<0.05) increase in ash (3.77±0.03%) and fbre content (2.08±0.03%) with an increasing amount of K. alvarezii powder added. The crude protein, crude fat, and moisture content decreased signifcantly (p<0.05) as more K. alvarezii powder was added. In conclusion, the incorporation of K. alvarezii powder in crackers showed improvement in the ash and crude fbre content and physical properties of the crackers.